Correlation between Branched Chain Amino Acids to Tyrosine Ratio and Child Pugh Score in Liver Cirrhosis Patients - Irsan Hasan; Rino A Gani; Nurul Akbar; Sjaifoellah Noer (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Background: The determination of branched chain amino acids (BCAA) to tyrosine ratio (BTR) was available in making differentiation of chronic hepatitis from liver cirrhosis, because there was a strong association between BTR and staging (fibrosis) scores. Branched chain amino acids to tyrosine ratio have a correlation with Fischer ratio and the examination is easier because it can be done by enzymatic assay. Materials and Methods: To evaluate the correlation between BTR and Child-Pugh score, we examined the amino gram of 52 liver cirrhosis patients consisted of 26 Child-Pugh A, 19 Child-Pugh B, and 7 Child-Pugh C. The examination of amino gram was done by High Pressure Liquid Chromatograph (HPLC) analyzer. Branched chain amino acids to tyrosine ratio were compared to Child-Pugh score, albumin, ammonia level, number connection test to Fischer ratio. Results: Significant differences in BTR among Child-Pugh A, B, C were observed (Child-Pugh A 7.75 + 1.2; Child Pugh B 6.0 + 1.23 and Child Pugh C 4.38 + 3.14 (p = 0.000)). Branched chain amino acids to tyrosine ratio had a weak correlation with albumin (r = 0.292; p = 0.036), ammonia level (r = 0.376; p = 0.006) and strong correlation with Fischer ratio (r = 0.818; p = 0.000). There was no significant correlation between BTR and number connection test. Conclusion: These results showed that the determination of the molar ratio of branched chain amino acids to tyrosine well reflected the severity of liver cirrhosis and it can be used as a substitute of Fischer ratio. Keywords: Branched chain amino acids, tyrosine, liver cirrhosis